2009
DOI: 10.1063/1.3234393
|View full text |Cite
|
Sign up to set email alerts
|

Structure, ionic conduction, and giant dielectric properties of mechanochemically synthesized BaSnF4

Abstract: Articles you may be interested inAlternative current conduction mechanisms of organic-inorganic compound [N(CH3)3H]2CuCl4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 31 publications
7
48
0
Order By: Relevance
“…In agreement with the study of Chadwick et al [7] this value represents one of the highest conductivities reported for BaSnF 4 when the mechanosynthesized product studied here is compared with samples prepared via other routes such as high temperature synthesis, wet chemical methods or other mechanochemical approaches including the various types of ball milling [4][5][6][7].…”
Section: Impedance Spectroscopysupporting
confidence: 91%
See 3 more Smart Citations
“…In agreement with the study of Chadwick et al [7] this value represents one of the highest conductivities reported for BaSnF 4 when the mechanosynthesized product studied here is compared with samples prepared via other routes such as high temperature synthesis, wet chemical methods or other mechanochemical approaches including the various types of ball milling [4][5][6][7].…”
Section: Impedance Spectroscopysupporting
confidence: 91%
“…Outstanding room temperature ionic conductivity has been found for tetragonal BaSnF 4 , which makes it a prospecting candidate for its application in both electrochemical storage systems and sensors. However, comparisons of published literature data points to a strong dependency of the conductivity on the preparation method applied [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the whole temperature range, we can see that the enhancement of measured temperature strengthens the grain boundaries effect gradually and weakens the grains effect at the same time. This is similar to many materials (Lin et al, 2008;Ahmad et al, 2009), where higher temperature stimulated the ions hopping over their barrier layers instead of hopping within their own sites.…”
Section: Electrical Modulussupporting
confidence: 70%